An Analysis of the Use of Transitive and Intransitive Verbs in Arabic: A Quantitative Descriptive Study of University Students in Malaysia: تحليل استخدام الأفعال المتعدية واللازمة في اللغة العربية: دراسة وصفية كمية لطلبة جامعة بماليزيا - Mohamad Rofian Ismail; Aiman Hakim Azemaizan; Azman Che Mat (Journal of Arabic Language Learning and Teaching (JALLT), 2026)
This study addresses a research gap concerning the limited empirical evidence on learners’ understanding and use of transitive and intransitive verbs in Arabic as a foreign language, particularly within the Malaysian higher education context. The study aims to examine students’ levels of comprehension and usage patterns of these verb types, as well as to identify related morphological difficulties. Adopting a quantitative descriptive approach, data were collected through a questionnaire administered to 91 undergraduate students enrolled in the LG 242 course at Universiti Teknologi MARA (UiTM), Malaysia. The data were statistically analyzed using SPSS, focusing on mean scores and standard deviations to determine students’ levels of understanding and usage. The findings indicate that students demonstrate a generally high level of understanding of transitive and intransitive verbs, with mean scores ranging from 3.60 to 4.14. However, persistent difficulties were identified in accurately distinguishing between the two verb types, largely due to insufficient mastery of Arabic morphological systems. The novelty of this study lies in its integration of morphological understanding with the functional use of verbs in daily communication, an aspect that has received limited attention in previous research. The findings contribute to the literature on Arabic language pedagogy and offer practical implications for enhancing instructional and assessment strategies in teaching Arabic morphology at the tertiary level.